2016
DOI: 10.1016/j.enzmictec.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A biosensor platform for rapid detection of E. coli in drinking water

Abstract: The need for rapid, specific and sensitive assays that provide a detection of bacterial indicators are important for monitoring water quality. Rapid detection using biosensor is a novel approach for microbiological testing applications. Besides, validation of rapid methods is an obstacle in adoption of such new bio-sensing technologies. In this study, the strategy developed is based on using the compound 4-methylumbelliferyl glucuronide (MUG), which is hydrolyzed rapidly by the action of E. coli β-D-glucuronid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…When E. coli metabolizes Collilert-18’s nutrient-indicator, MUG, the sample also fluoresces. It is reported that the method is able to detect a single viable coliform or E. coli per sample and eliminates false positive detection of non-target organisms [5,6,7,8,9,10,11,12]. For each test, contents of one pack of Collilert-18 were added to a 100 mL sample in a sterile, transparent, non-fluorescing vessel which was then capped and shaken.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When E. coli metabolizes Collilert-18’s nutrient-indicator, MUG, the sample also fluoresces. It is reported that the method is able to detect a single viable coliform or E. coli per sample and eliminates false positive detection of non-target organisms [5,6,7,8,9,10,11,12]. For each test, contents of one pack of Collilert-18 were added to a 100 mL sample in a sterile, transparent, non-fluorescing vessel which was then capped and shaken.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we identified specific bacterial enzymatic-biochemical signatures that can be used in a custom designed opto-electronic biosensor platform for the detection of E. coli and other bacterial cells in water samples [5,6]. The new generations of biosensors rely on bacterial enzymatic responses to specific fluorogenic substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 With this handheld fluorescence detector, the E. coli concentrations of 7 CFU/mL are detected within 30-60 min after testing. Similarly, Hesari, et al, 43 developed custom designed fluorescence biosensor to detect E. coli. This method also uses the enzymatic activity of the MUG substrate with the β-D-glucuronidase enzyme.…”
Section: Rapid Water Quality Test Methodsmentioning
confidence: 99%
“…Several sensors for water quality monitoring have been designed and developed for rapid detection of bacteria (total coliform and E. coli) in water samples. They are a paper-based microfluidic method, handheld fluorometer, [42][43][44] Mobile Water Kit, [45][46][47] hydrogel-based plunger-tube assembly, [48][49][50] and glucometer based detection. 51 We provide the details of each method briefly.…”
Section: Rapid Water Quality Test Methodsmentioning
confidence: 99%